Analysis of the Level of Implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on the Quality of MSME Financial Reports in Manado City - Jeshlyn Evania Stefanny Rombang; Jenny Morasa; Midian C. Rori (International Journal of Economic and Business Research, 2026)
This study examines the level of implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and its effect on the quality of MSME financial reports in Manado City. A quantitative approach with a causal associative design was employed, using simple linear regression analysis. Primary data were collected through structured questionnaires distributed to 80 MSME owners selected using purposive sampling. The research instrument was evaluated through validity and reliability tests, while the regression model was assessed using classical assumption tests before hypothesis testing. The findings indicate that the implementation of SAK EMKM among MSMEs is generally categorized as good, with an average implementation score of 57.01 out of a maximum of 65, although weaknesses remain in the preparation of Notes to the Financial Statements (CALK). Hypothesis testing reveals that the implementation level of SAK EMKM has a positive and statistically significant effect on the quality of MSME financial reports (t = 11.509; p < 0.001). The coefficient of determination (R² = 0.629) demonstrates that 62.9% of the variation in financial reporting quality is explained by the level of SAK EMKM implementation. These findings highlight the importance of strengthening accounting standard implementation to improve the transparency, reliability, and decision usefulness of MSME financial reporting.